EEG changes in Autism spectrum Disorder in tertiary care hospital - Paul, Bikush Chandra; Islam, Kazi Ashraful; Akther, Shaheen; Fatema, Kanij; Shefa, Jannatara (Advances in Social Sciences Research Journal, 2017)
Introduction: ASD is a neuro-developmental disorder characterized by impairment of communication, behavior and socialization. About a third of children with ASD have epilepsy. Most of the cases are associated with some form of movement disorder mimicking epilepsy. However, few cases show epileptiform discharge on EEG without clinical seizure. Rationale: Seizure and pseudoseizure differentiation is important issue in ASD cases to administer AED. Method: Sixty children with ASD had undergone EEG. A questionnaire was filled up with clinical parameter and EEG findings. All findings were analyzed. Result: Mean age at presentation was 36 months. M:F ratio was 3:1. All children presented with core symptom of impairment in verbal and nonverbal communication and behavior problem. EEG was abnormal in 47% case.Among them focal discharge 6(10%), generalized discharge 16(17%), others 6(10%) were found. Conclusion: Fair number of EEG changes was present in ASD cases without symptomatic seizure. This cases need further evaluation for management.